Предмет: Алгебра,
автор: Иван7
lg(x-1) + lg(x+1) = lg(9x+9)
Ответы
Автор ответа:
0
lg(x-1) + lg(x+1) = lg(9x+9) ОДЗ x>1
lg(x-1)(x+1) = lg(9x+9)
x^2-1=9x+9
x^2-9x-10=0
x1=10
x2=-1 не подходит ОДЗ
Ответ х=10
Автор ответа:
0
Преобразуем по свойствам логарифма и получим простое уравнение:
(x-1)(x+1)=9x+9
D=121
X=10
X=-1 ( Не забываем про ОДЗ!!!)
Ответ: 10.
Похожие вопросы
Предмет: Химия,
автор: animebrat1
Предмет: География,
автор: Аноним
Предмет: История,
автор: Аноним
Предмет: Геометрия,
автор: Самородок
Предмет: Обществознание,
автор: sania28